Preliminary evaluation of the gut microbiota modulatory potential of Malaysian kefir water in ageing m ice - Rajah Kumar, Muganti; Amankwaa, Aaron Opoku; Razali, Nurulain Syahirah; Mohamad, Nurul Elyani; Khalid, Melati; Abdullah, Janna Ong; Masarudin, Mas Jaffri; Osman, Mohd Azuraidi; Nik Abd Rahman, Nik Mohd Afizan; Alitheen, Noorjahan Banu (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Ageing is often accompanied by gut microbiota alterations that contribute to dysbiosis—a recognised hallmark of ageing and a risk factor for neurodegenerative diseases. Probiotic interventions offer a promising approach to restore microbial homeostasis. This preliminary study explored the potential modulatory effects of Malaysian kefir water, a Lactobacillus-enriched fermented beverage with previously reported antioxidant and neuroprotective properties in D-galactose-induced ageing mice. Kefir water was administered as both a pre-treatment and co-treatment, and gut microbiota changes were assessed using 16S rRNA metagenomic sequencing of faecal samples. Alpha and beta diversity analyses showed a stable microbial diversity across treatments. However, preliminary descriptive trends suggested that kefir water may influence specific bacterial populations. Increases were observed in Muribaculaceae and Lactobacillaceae, along with apparent decreases in Lachnospiraceae and Prevotellaceae. Both kefir treatments tended to increase the abundance of Ligilactobacillus, with the co-treatment group appearing to restore the Firmicutes/Bacteroidota ratio toward control levels, while the pre-treatment group showed a tendency to further reduce this ratio. Collectively, these findings provide preliminary indications that kefir water may hold potential as a dietary approach to modulate gut microbial changes associated with ageing. However, confirmation through studies with larger sample sizes and broader analytical coverage is necessary to substantiate these initial observations.